Penyelesaian Putusan Sengketa Ekonomi Syariah Pada Perkara Wanprestasi BMT Al-Falah Berkah Sejahtera di Pengadilan Agama Sumber - Muamar, Afif; Rohayati, Fadilah (Recital Review, 2024)
The purpose of this research is to analyze the handling of Sharia economic disputes, especially in cases of default in religious courts, and the source of the decision. This research shows that the settlement of sharia economic cases is regulated in Supreme Court Regulation (PERMA) Number 14 of 2016 concerning Procedures for Settling Sharia Economic Cases. Furthermore, Article 1243 of the Civil Code states, "Reimbursement of costs, losses, and interest for non-fulfillment of an obligation begins to be required if the debtor, even though it has been declared negligent, remains negligent to fulfill the obligation, or if something that must be given or done can only be given or done in a time that exceeds the time specified.". Thus, through the judge's decision, it is decided that defendants I and II, who have been officially and properly summoned, are not present at the trial, so it is considered that the allegations made by the plaintiff are true and that the defendant has defaulted. Stating that the decision of this case is declared to be executable in advance even though there is a verzet, punishing Defendant I and Defendant II to pay immediately and unconditionally the entire remaining debt to the Plaintiff in the amount of Rp. 112,600,000, unable to pay it, the land certificate will be auctioned to pay off the financing.